Peran Guru dalam Implementasi Strategi Pembelajaran Ekspositori dalam Pembelajaran - Supardi Ritonga; Mir'atun Nabila; Ulfa Rahma Dhini; Resty Junianti; Zulkarnain Syah (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2024)
Certain students still have difficulty understanding the lessons given by the teacher. Expository learning is a learning approach that emphasizes the process of conveying material to a group of students orally. The goal is to improve students' ability to learn and master subject matter in the most effective way, so that students can understand what is being taught. The authors used the bibliographic research method, or bibliography, to write this journal, and they used various reading sources as references. Expository strategies can be used in learning, this is done to achieve learning goals and make learning take place effectively and efficiently.